Land Asset Management Case Study of Asset in Gorontalo District Government - Djafar, Pandi; Karim, Dian Fitriani; Akbar, Muh. Firyal; Djafar, Franky (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Land asset management in Gorontalo Regency faces various problems, including weak inventories, late reporting by Regional Apparatus Organizations (OPD), and the persistence of uncertified assets and overlapping ownership documents. These conditions indicate that land asset management is not yet optimal. This study aims to describe and analyze land asset management in the Gorontalo Regency Government, focusing on planning, implementation, and supervision. The method used was a qualitative approach with a descriptive approach. Data were obtained through observation, in-depth interviews with the Regional Personnel Agency (BKAD) and Commission II of the Regional People's Representative Council (DPRD), and documentation. Analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. The results indicate that planning is not optimal due to weak coordination and data integration. Implementation is still hampered by recording, assessment, and certification due to limited human resources. Supervision has been carried out through document review, but is hampered by late reporting and a lack of transparency. The conclusions of this study confirm that land asset management in Gorontalo Regency is not yet effective and efficient, necessitating strengthening coordination, inventory systems, human resource quality, and transparent supervision.